CASE STUDIES REGARDING THE EFFECTIVENESS OF MANAGERIAL DECISION MAKING ARE ASSOCIATED WITH BED TURN OVER(BTO) IN SEMBIRING DELI TUA PUBLIC HOSPITAL, DELI SERDANG DISTRICT, IS NEAR IN, 2018 - MIFTAHUL JANNAH (JURNAL ILMIAH KOHESI, 2020)
Medical records that should be used as a source of information in the decision making process at the hospital, are still facingproblems. Information that supports medical record data in managerial decision making, namely the utility of inpatient care,inpatient service quality, and the biggest disease in Sembiring Hospital, it can be seen from the medical record data aboutbed occupancy rate (BOR), Bed turn over (BTO) , length of stay (LOS), internal turnover (TOI) from 2015 to 2018 can beseen that the use of beds in hospitals has not fulfilled standard value of the health service parameters and of the five biggestdiseases in Sembiring Hospital is one of file bigjust disease, therefore sembiring hospital managers Sembiring took a policythat is adding an inpatient room. The aim of the study was to determine the effectiveness of managerial decisions associatedwith bed turn over at Sembiring hospital. The research method used is qualitative research, with the design of a single casestudy design striking. in general the process of decision-making activities has been done well by managerial SembiringHospital, but this process is still ineffective, because the decisions taken by Sembiring General Hospital have not been fullyimplemented, there are still obstacles in implementing decisions, Sembiring Hospital manager has not been fully entitled indecision making , and also the efforts made by the hospital management have not been able to fully overcome the problemof bed turn over.